An optical parametric oscillator for a light- atomic media interface - Andrade, Rayssa Bruzaca de (2018)
In this work, we discuss a description of quantum properties of light beams produced by an Optical Parametric Oscillator (OPO) above threshold, pumped by a 780 nm Titanium Sapphire laser, resonant with the D2 line of Rb with a noise spectrum of a coherent beam. The twin beams have wavelengths around 1560nm, in the telecommunication band. The states emitted by the OPO under study are approximately Gaussian (1), which allows us to describe them in terms of first and second order moments. As we analyze the noise spectrum of the fluctuations of each beam, the first order moments are null, which allows us to describe the state of the system in terms of a covariance matrix. We present the behavior of the noise spectrum and the correlations between the reflected pump, signal and idler beams. In addition, we applied different entanglement criteria to study the system. We present a prediction of the bipartite entanglement using Duan criterion (2). For tripartite correlations, we use the Furusawa criterion (3). We performed a study of bipartition pump and sum quadrature. As well, we applied the PPT criterion (4) for continuous variables, independently transposing each beam under study. The PPT criterion is necessary and sufficient to demonstrate entanglement between bipartitions for Gaussian states. In order to explore the behavior of the system using the steering criterion in the model developed by Reid (5), we theoretically study the criterion of inference for bipartite quadratures: between the twin beams or between one of the twin beams and the pump beam. In addition, we analyzed the inference between the three modes, through the bipartition pump mode and combination of sum quadrature of the twin beams. We develop a quantum teleportation protocol of a coherent input state, composed by the Titanium Sapphire beam whose Bell measurement is performed using the pump reflected by the OPO as an entangled state for the signal and idler beams as a first possibility to implement the protocol. Furthermore, we propose a protocol in which the signal beam assists in the process of teleportation. Thus, the fidelity of the system increases and exceeds the limit of non-cloning. We will describe the first measurements of correlations between the beams emitted by the OPO for this system. The tripartite entanglement characterization is the first step in the implementation of quantum optical protocols using a source of entangled states that is compatible with both Rubidium atomic systems and the telecommunications region, thus forming a quantum network.